Atomistic simulations of friction at an ice-ice interface - Samadashvili, N.; Reischl, Bernhard; Hynninen, T.; Ala-Nissila, T.; Foster, A. (2013)
Even though the slipperiness of ice is important both technologically and environmentally and often experienced in everyday life, the nanoscale processes determining ice friction are still unclear. We study the friction of a smooth ice-ice interface using atomistic simulations, and especially consider the effects of temperature, load, and sliding velocity. At this scale, frictional behavior is seen to be determined by the lubricating effect of a liquid premelt layer between the sliding ice sheets. In general, increasing temperature or load leads to a thicker lubricating layer and lower friction, while increasing the sliding velocity increases friction due to viscous shear.